2017
DOI: 10.1186/s40880-017-0200-0
|View full text |Cite
|
Sign up to set email alerts
|

The 150 most important questions in cancer research and clinical oncology series: questions 6–14

Abstract: To accelerate our endeavors to overcome cancer, Chinese Journal of Cancer has launched a program of publishing 150 most important questions in cancer research and clinical oncology. In this article, nine more questions are presented as followed. Question 6. Why do nasopharyngeal carcinomas rarely metastasize to the brain? Question 7. Can distant spread of cancer cells be blocked by inhibiting the remodeling of high endothelial venules in the sentinel lymph node? Question 8. What sort of live-imaging techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…As reported in previous studies, nearly 25% of CRC cases are clinically diagnosed with liver metastasis during initial stage, and approximately 50% of CRC carriers develop liver metastasis symptoms during the course of the disease. Approximately 30-50% of patients with CRC develop recurrent liver metastases after radical resection, and more than 50% among them succumb to the disease 5 . Lungs are the second most common site of distant metastases in CRC 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…As reported in previous studies, nearly 25% of CRC cases are clinically diagnosed with liver metastasis during initial stage, and approximately 50% of CRC carriers develop liver metastasis symptoms during the course of the disease. Approximately 30-50% of patients with CRC develop recurrent liver metastases after radical resection, and more than 50% among them succumb to the disease 5 . Lungs are the second most common site of distant metastases in CRC 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its inherent characteristics, distant metastasis (DM) is more commonly observed in NPC than other head and neck squamous cell carcinoma (HNSCC) 5. It is reported that 4–10% of patients with NPC present with synchronous metastasis (smNPC, metastasis at initial diagnosis) 6.…”
Section: Introductionmentioning
confidence: 99%
“…NPC is distinct from other head and neck cancers due to its high rates of distant metastasis, including synchronous metastasis (smNPC, metastasis at initial diagnosis) and metachronous metastasis (mmNPC, metastasis over 6 months after radical chemoradiotherapy). 1 3 The incidences of smNPC and mmNPC have been reported to be 4%−10% and 15%–30%, respectively. 4 6 When metastasis occurs, the survival outcomes of patients are unsatisfactory with a median overall survival (OS) of 12–30 months after multidisciplinary therapies.…”
Section: Introductionmentioning
confidence: 99%